TAX AMNESTY - Suyanto Suyanto; Pasca Putri Lopian Ayu Intansari; Supeni Endahjati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
This study aims to determine the taxpayer's perception about the Tax Amnesty to compliance of the individual taxpayer. The nature of this research is a descriptive study with a quantitative approach. The method of analysis in this research is to use simple regression. Questionnaires are processed a total of 41 questionnaires. Results from this study is the perception Taxpayer positive effect on tax compliance. Based on test results, the obtained value of t arithmetic amounted to 3.244 higher than the t value is 1.6829 with a significance value of 0.002, thus Ha supported. Keyword: Tax Amnesty Program, Taxpayer’s Complience.